Urologic Oncology Multidisciplinary Care for Patients - Stratton, Kelly L.; Morgans, Alicia K.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2022)
Urologists and medical oncologists have witnessed a rapid growth in systemic therapeutic options for treating genitourinary malignancies that increasingly integrates radiation therapy to primary cancers, nodal beds, and even metastatic sites. The culmination of these advances has been the creation of multidisciplinary teams that expertly provide comprehensive care to patients with urologic cancers. This book provides the framework to create such a multidisciplinary clinical team focused on the treatment of urologic malignancies with representation from urologists, medical oncologists, and additional specialists who work together to provide optimal team-based care. The book integrates advanced systemic therapeutics including immune-based and targeted therapies. Readers gain a better understanding of the benefit of multidisciplinary co-management through specific examples such as hormone sensitive metastatic prostate cancer, neoadjuvant chemotherapy for muscle invasive bladder cancer, and immunotherapy approaches to advanced bladder and kidney cancer. The book also discusses the integration of genomic tumor characterization and personalized medicine into surgical planning, tumor biopsies, and chemo-immunotherapy selection, emphasizing the expansion of new therapeutics for urologic malignancies and the changing definitions of disease progression. Urologic Oncology: Multidisciplinary Care for Patients is a comprehensive resource for urologists, medical oncologists, radiation oncologists, genetic counselors, fellows in urologic oncology and medical oncology, residents in urology and radiation oncology, advanced practice providers, practice managers, and pharmaceutical representatives. .
Creating a Multidisciplinary GU Cancer Clinic -- Supportive and Palliative Care for Genitourinary Malignancies -- Operationalizing Genetic Testing in the Care of Patients with Prostate Cancer -- High-Risk Prostate Cancer -- Treatment of Metastatic Hormone Sensitive Prostate Cancer -- Expanding Options for M0 Castration Resistant Prostate Cancer (CRPC) -- Immunotherapy for Metastatic Prostate Cancer -- Advances in Prostate Cancer Imaging -- Bone Health Management -- Radiotherapy for Advanced Prostate Cancer -- Optimizing Perioperative Treatment for Kidney Cancer -- Surgical Treatment for Metastatic Kidney Cancer -- Targeted Therapy for Renal Cell Carcinoma -- Hereditary Cancer and Genetics in Renal Cell Carcinoma -- Immunotherapy in Renal Cell Carcinoma -- Evolving Treatment in Non-Muscle Invasive Bladder Cancer -- Neoadjuvant and Adjuvant Therapy for Muscle-Invasive Bladder Cancer -- Bladder-Sparing Approaches to Treatment of Muscle-Invasive Bladder Cancer -- Treatment of Metastatic Bladder Cancer -- Treatment of Upper Tract Urothelial Carcinoma.
Keywords: Internal medicine; Internal Medicine; Urologic Neoplasms